2020
DOI: 10.7717/peerj.9043
|View full text |Cite
|
Sign up to set email alerts
|

Linking diffuse radiation and ecosystem productivity of a desert steppe ecosystem

Abstract: Radiation components have distinct effects on photosynthesis. In the desert steppe ecosystem, the influence of diffuse radiation on carbon fixation has not been thoroughly explored. We examined this diffusion and its effect on ecosystem productivity was examined during the growing season from 2014 to 2015 on the basis of eddy covariance measurements of CO2 exchange in a desert steppe ecosystem in northwest China. Our results indicated that the gross ecosystem production (GEP) and diffuse photosynthetically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…On cloudy days, the enhancement of α and P 1800 in low T a and VPD were higher than in high T a and VPD ( Table 2 ). It is similar to those results that were found in a poplar plantation ( Xu et al., 2017 ) and a desert steppe ( Li et al., 2020 ). Under cloudy sky conditions, low T a and VPD were more conducive to enhancing canopy photosynthesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On cloudy days, the enhancement of α and P 1800 in low T a and VPD were higher than in high T a and VPD ( Table 2 ). It is similar to those results that were found in a poplar plantation ( Xu et al., 2017 ) and a desert steppe ( Li et al., 2020 ). Under cloudy sky conditions, low T a and VPD were more conducive to enhancing canopy photosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies, however, indicated that T a and VPD had little effect on regulating the ecosystem photosynthesis response to I f ( Jing et al., 2010 ; Kanniah et al., 2011 ; Oliphant et al., 2011 ). Changes in environmental conditions may affect GPP response to I f of forest and grassland ecosystems ( Xu et al., 2017 ; Li et al., 2020 ). The coupling between DF and environmental factors will have complex effect on ecosystem photosynthesis ( Kanniah et al., 2013 ; Gui et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The light response curves under different sky conditions showed similar trends, and the curves under overcast conditions increased more steeply with PARt. This result was consistent with previous research (Li et al, 2020;Oliphant et al, 2011;Williams et al, 2014). The response of photosynthesis to sky conditions varied across seasons (Table 1).…”
Section: The Effects Of Diffuse Radiation On Ecosystem Photosynthetic...supporting
confidence: 93%
“…where PARd and PARb was the diffuse and the direct photosynthetically active radiation (μmol m -2 s -1 ), respectively. In most previous studies, sky conditions were only classified as clear or cloudy conditions (Alton, 2008;Li et al, 2020;Xu et al, 2017), and the difference in NEP between cloudy and overcast conditions had not been determined. In this study, we divided sky conditions using daily average CI into sunny (0.6 ≤ CI < 1), cloudy (0.2 ≤ CI < 0.6) and overcast (0 < CI < 0.2) conditions according to Reindl et al, (1990).…”
Section: Cloudiness and Diffuse Radiationmentioning
confidence: 99%
See 1 more Smart Citation